Emotional appeal in ChatGPT prompts: A study of L2 speakers’ perceptions - Iryna Morozova; Valeriia Nikolaienko (Res Rhetorica)
This article investigates the rhetorical means used by EFL university students in interactions with ChatGPT with emotional prompts. It has been found that most participants do not construe the interaction with the bot as a traditional communicative situation, and do not frame the bot as a humanlike agent. However, after being prompted to use emotional appeal, the participants mapped the features of human-human communicative situation without mapping the perception of the interlocutor as a human being.